The form and function processing of lexical tone and intonation in tone-language-speaking children with autism spectrum disorder - Wang, Li (2023)
Studies on how the form versus function aspect of tone and intonation is processed by autistic individuals have mainly focused on speakers of non-tonal languages (e.g., English) with equivocal results. While the samples' heterogeneous cognitive abilities may be contributing factors, the phenotype of tone and intonation processing in autism may also vary with one's language background. Thirty-eight cognitively able autistic and 32 non-autistic Mandarin-speaking children completed tone and intonation perception tasks, each containing a function and form condition. Results suggested that the abilities to discriminate tone and intonation were not impaired at either the form or function level in these autistic children, and that these abilities were positively associated with one another in both autistic and non-autistic groups. The more severe the autism symptoms, the worse the form- and function-level of tone and intonation processing. While enhanced tone and intonation processing has been found in a subgroup of autistic children, it may not be a general characteristic of the autistic population with long-term tone language experience. These findings reveal typical tone and intonation processing at both the form and function levels in cognitively able Mandarin-speaking autistic children and provide evidence for associated tone and intonation processing abilities across levels.